b=根号[(2a-b)/(4a+3b)]+根号[(b-2a)/(4a+3b)]+3/2 ,则a²-ab+b&s
1个回答
27/16
因为:根号[(2a-b)/(4a+3b)]、根号[(b-2a)/(4a+3b)]都成立
根号下必须>=0
所以:2a-b=0
b=3/2 => a=3/4
a²-ab+b²=27/16
相关问题
已知根号a(根号a+根号b)=3根号b(2/3根号a+4根号b)(ab≠0).求(a-2b+根号ab)/(a+b+根号a
2b根号a/b+3/a根号a立方b-(4a根号b/a+根号9ab)
已知根号a(根号a+根号b)=6根号b(根号a-根号b) 求a-2根号ab+3b除以2a-3根号ab+4b
已知a>0,b>0,且根号a*(根号a+4根号b)=3根号b(根号a+2根号b),则(a+6根号a*b-8b)/2a-3
若(a+根号3/a-根号3)+(b-根号3/b+根号3)=2+根号6,a-b=2根号2,求ab.
有理数ab满足a+2b+根号2=3+(a-b)乘根号2,则a=____,b=____
1(a^4/3-8a^1/3b)/(4b^2/3+2三次根号ab+a^2/3)/(1-2三次根号b/a)*三次根号a
若a,b为实数,且b<根号a-2+根号2-a+2,化简:3/2-b根号b平方-4b+4+根号2a
计算.根号(a^3b^2乘以3根号ab^2)/(a^1/4乘以b^1/2)^4乘以3根号b/a
已知a-b=2根号3-1,ab=根号3则(a+b)(a-b)等于